Students’ Critical Thinking Of Explanation Writing - Linda Mayasari; Ria Novia (Universitas Muhammadiyah Surabaya, 2019)
This research paper aims to describe the use of task-based learning strategy in teaching learning writing explanation at tenth grade of senior high school. The research focused on the use of task-based learning strategy to improve students’ critical thinking ability in explanation writing. This classroom action research consists of one cycle and in the cycle consisted of four steps: planning, action, observation, and reflection. The subject of this research was the students of tenth grade in SMA Negeri 13 Surabaya. In analyzing and collecting the data, it used the information from the interview, observation in the class and the achievement of the students’ writing. Brown’s theory and Willis’ theory were utilized to find out more about the writing and critical thinking of students’ in writing explanation through task based learning. Based on the analysis, it can be seen through TBL, the students were able to perform six components of critical thinking suggested by NEIU’s in CTL (the issues, context, perspective, assumption, evidence and implication) in their explanation writing under the topic eco-composition. Key words: Writing, Task-Based Learning, Eco-composition, Critical Thinking.